Analysis of Hard Box Product Failures Using Failure Mode and Effects Analysis (FMEA) and DMAIC Methods at PT XYZ - Mellyani Nurmaya Fauzizah; Hendi Herlambang; Setiawan `Setiawan (Journal La Multiapp, 2026)
PT XYZ is a manufacturing company in the packaging industry that produces hard box products with high precision requirements. Based on production data from January to December 2025, the defect rate reached an average of 3.39% with a maximum value of 6.80%, exceeding the company standard of 3%, indicating that the production process is not yet fully under control and requires systematic quality improvement. This study aims to identify dominant defect types, analyze the root causes of failures, and determine effective improvement priorities. The method used is the DMAIC (Define, Measure, Analyze, Improve, Control) approach integrated with Failure Mode and Effect Analysis (FMEA) to assess failure risks based on the Risk Priority Number (RPN). The results show that the dominant defects are dimensional inaccuracy (22.91%), glue contamination (20.76%), and dented/damaged products (18.82%), contributing 62.49% of the total defects. Based on FMEA analysis, glue contamination has the highest RPN value of 384, making it the top priority for improvement. The main causes of defects are related to human factors, machine conditions, and unstandardized work methods. The proposed improvements include process standardization, development of standard operating procedures (SOP), use of supporting tools, enhancement of operator competence, and regular machine maintenance and calibration. The integration of FMEA within the DMAIC framework provides a more systematic and structured analytical approach and is projected to reduce the defect rate to meet or approach the company’s quality standard.